The Management Of Vocational School (A Site Study at SMK Pelita Bangsa Sumberlawang Sragen) - Widodo, Teguh (2012)
This research has four objectives, to describe the Vocational School Curriculum, Human Resources, Facilities, and Funds at SMK Pelita Bangsa Sumberlawang Sragen. It is a qualitative research using ethnography design. The main research subject consists of the principal, teachers, and students. Data collection method used interview, observation, and documentation. Data analysis was started by (1) data collection, (2) data reduction, (3) data display, and (4) drawing conclusion. Data validity used credibility, transferability, confirmatbility, and dependability. The findings suggest that Vocational school curricula at SMK Pelita Bangsa Sumberlawang Sragen is compiled in a team by focusing on intellectual aspects of students and also the character of students. The compiled curriculum contains the adaptive, normative, productive and local content subject matters and also self-development through extracurricular activities and entrepreneurship program. Curriculum evaluation is done by looking at the achievement of any program implemented by the school. Human resources at SMK Pelita Bangsa Sumberlawang Sragen have a good competence. It is seen from the students' achievements in the Olympiad activities, although it is classified as a new school in Sragen. This is not apart from a credible form of recruitment and competence development program organized by the school. Competence development program organized by the school include motivation, implementation, supervision, and also sending teachers in the deliberation of subject matter teachers. Facilities of vocational school at SMK Pelita Bangsa Sumberlawang Sragen still need to be completed such as the computer repair shop, props, and reference books. Although the facility is not yet complete, the school has made a special team to manage the facilities. Currently the school is focusing on building a class, and will continue on the construction of the laboratory room. Financing of vocational school at SMK Pelita Bangsa Sumberlawang Sragen is done transparently in which all revenues and expenditures or expenses, including costs to the public are informed to parents. The school funding is managed by the school treasurer, head of administrative, and the principal. Costs to be incurred by the school are allocated to the needs of students, building construction, and complete the facilities to support teaching and learning activities as well as fulfilling teachers' welfare.